Huaier Suppresses Breast Cancer Progression via linc00339/miR-4656/CSNK2B Signaling Pathway - Wang, Wei; Wang, Xiaolong; Li, Chen; Chen, Tong; Zhang, Ning; Liang, Yiran; Li, Yaming; Zhang, Hanwen; Liu, Ying; Song, Xiaojin; Zhao, Wenjing; Chen, Bing; et al. (Frontiers in Oncology, 2019)
Huaier, as known as Trametes robiniophila Murr, is a traditional Chinese medicine.Various studies have demonstrated that Huaier could inhibit cancer progression and improve the prognosis of patients. In the present study, we comprehensively screened the expression profiles of lncRNAs, miRNAs and mRNAs in Huaier-treated breast cancer cells. Using bioinformatic analysis, hub genes were identified and functionally annotated. Weighted gene coexpression network analysis was applied to construct the molecular network influenced by Huaier. Linc00339 was then found to play a critical role in Huaier-mediated cancer suppression. To validate the effects of linc00339 and identify the downstream targets, we performed in vitro and in vivo experiments. Finally, we identified that Huaier could inhibit the proliferation of breast cancer cells through modulating linc00339/miR-4656/CSNK2B signaling pathway.